Curriculum Management In Improving The Quality Of Education - Muhammad Indra Adi Gunawan; Eng Fadly Usman (Journal of Social Science and Economics, 2022)
Basically, curriculum management has three stages, namely planning, implementation and evaluation. The three stages of management are integrative which determine the success of the school curriculum. Curriculum management is one of the important components in an educational institution where curriculum management is very influential on the quality of education. Education is said to be of quality if it has succeeded in creating outputs whose results are in accordance with the goals that have been set. The purpose of this study was to determine the planning, implementation and evaluation of curriculum management in improving the quality of education at SMA Al-Azhar Menganti. This research uses a qualitative approach with the type of case study research. Data collection is done by observation, interviews, and documentation. Data analysis uses data reduction, data presentation and data verification. Based on the results of the research that has been done, it can be concluded that curriculum planning begins with the formation of a quality assurance team that will prepare a context and SWOT analysis, then based on the results of the analysis a curriculum development team is formed which will compile curriculum documents at the education unit level. Implementation of the curriculum begins with socialization and training to teachers in preparing learning tools. then the evaluation process is carried out with learning supervision, teacher performance assessment, monthly evaluation and evaluation at the end of the school year.